Inovação no processo de desenvolvimento de novos produtos de uma empresa fabricante de alto-falantes a partir do design estratégico: formalização de uma etapa metaprojetual - Cruz, Roberto Thomé da (Universidade do Vale do Rio dos Sinos, 2011)
The present study addresses the process of developing of new products (PDNP) from a loudspeaker’s manufacturer (Eletrônica Selenium S.A.) in view of its current context given the early stages of their development processes in order to analyze and propose changes to these processes aimed at increasing the innovation potential and competitiveness through the development of a formal, systematic and collaborative idea generation environment and the use of the tools of strategic design. For this study, the research relied on interviews with professionals working in product development (experts) and studying the processes of product development of companies surveyed. From the data obtained, was held the critical analysis of the current model of product development and the appointment of potential improvement opportunities. As a result of this discussion, was presented two proposals for models for the flow of product development with a focus on innovation and driven by strategic design: the first is in a complex model with the inclusion of metaprojetual model, whose implementation requires changes in cultural, process and structural of the organization, which can mean heavy investments with returns in the long term and the second model, presents a more simplified logic with a focus on blue sky research with a view to implementation easier not requiring significant changes in cultural, process and structural of the organization, with low investment and whose results can arise in the short term. The conclusions discuss the implications involved in the changes in product development processes such as culture, structure, modes of administration and that reveal themselves as obstacles to its deployment.
Keywords: Design estratégico; Metaprojeto; Processos de desenvolvimento de novos produtos; Inovação; Strategic design; Metaproject; Development of new products process; Innovation; ACCNPQ::Ciências Sociais Aplicadas::Desenho Industrial